Inflammatory microenvironment in classical Hodgkin’s lymphoma with special stress on mast cells - Ribatti, Domenico; Tamma, Roberto; Annese, Tiziana; Ingravallo, Giuseppe; Specchia, Giorgina (Frontiers in Oncology, 2022)
Classical Hodgkin’s lymphoma (CHL) accounts for 10% of all lymphomas. Nodular sclerosis and mixed cellularity accounts for nearly 80% of all CHL cases. The number of mast cells in CHL correlates with poor prognosis, is significantly higher in nodular sclerosis than in other CHL subtypes, and an association between the degree of angiogenesis and the number of intratumoral mast cells has been demonstrated in CHL. Even with the best available treatment, a significant percentage of CHL patients progress or relapse after first-line therapy. 50% of patients with disease relapse achieve subsequent long-term disease control with salvage therapies. In this context, new potential therapeutic opportunities are required, and mast cells may be regarded as a new target for adjuvant treatment of CHL through the inhibition of angiogenesis and tissue remodeling and allowing the secretion of cytotoxic cytokines.